1998
DOI: 10.1063/1.477710
|View full text |Cite
|
Sign up to set email alerts
|

Nonequilibrium statistical thermodynamics: Nonequilibrium grand ensemble method for sheared dilute gases

Abstract: The nonequilibrium grand ensemble method previously reported is rigorously implemented for a nonequilibrium dilute gas mixture sheared in plane Couette flow geometry and analytic results are presented for the nonequilibrium thermodynamic quantities of the sheared gas. The calortropy is shown to contain all the constitutive information of the system. The notions of temperature and pressure for the nonequilibrium gas are examined on the basis of the calortropy calculated from the nonequilibrium grand partition f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Farhat and Eu (1998), who also included normal-pressure effects in a non-equilibrium ensemble method proposed by Eu (1998). Note that (2.32) could also be written as M = (k B T ) −1 U + λ , with the component of λ defined accordingly.…”
Section: Information Analysis Of An Ideal Gas Under Viscous Pressurementioning
confidence: 99%
“…Farhat and Eu (1998), who also included normal-pressure effects in a non-equilibrium ensemble method proposed by Eu (1998). Note that (2.32) could also be written as M = (k B T ) −1 U + λ , with the component of λ defined accordingly.…”
Section: Information Analysis Of An Ideal Gas Under Viscous Pressurementioning
confidence: 99%
“…There are a number of ways to close the open hierarchy. We have found that the following closure gives rise to a structure of generalized hydrodynamics consistent with irreversible thermodynamics and at the same time a divergence free non-equilibrium statistical mechanics which enables us to calculate the non-equilibrium partition function (Al-Ghoul & Eu 2001a;Farhat & Eu 1998). Such a closure is (Al-Ghoul & Eu 1997, 2001b)…”
Section: Generalized Hydrodynamic Equationsmentioning
confidence: 86%